(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper discusses the issue of management of E-Waste (EW) in India, driven by the rising consumption of electronic products. EW is a global problem as it is dangerous to human health and the environment due to the presence of toxic chemicals. In India, the informal sector is a dominant player in managing EW, which uses crude recycling methods that further worsens the issue. Even after the E-Waste Management Rules 2016, formal sector compliance and infrastructure are absent. This paper assesses the current situation, identifies the challenges, and offers recommendations such as improving infrastructure, enhancing legislation, awareness campaigns, and encouraging formal recycling. India can learn from the best practices prevalent globally, like the stringent laws of Switzerland and the technological advancement of Japan, and so forth to improve its EW management and reduce health risks.